A stochastic model for earthquake slip distribution of large events. Issue 2 (3rd March 2016) - Raghukanth, S.T.G.; Sangeetha, S.
Abstract : This paper presents a stochastic model to simulate spatial distribution of slip on the rupture plane for large earthquakes ( Mw >7). A total of 45 slip models coming from the past 33 large events are examined to develop the model. The model has been developed in two stages. In the first stage, effective rupture dimensions are derived from the data. Empirical relations to predict the rupture dimensions, mean and standard deviation of the slip, the size of asperities and their location from the hypocentre from the seismic moment are developed. In the second stage, the slip is modelled as a homogeneous random field. Important properties of the slip field such as correlation length have been estimated for the slip models. The developed model can be used to simulate ground motion for large events.